Implementasi Metode Proof of Reserve pada Sistem Pengiriman Barang untuk Menjaga Integritas Data - Dwi Saidina Zulfela Sembiring; Ardiansyah Putra; Alex Zander Siregar; Alfito Surya Pradana; Rico Wijaya Dewantoro (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
This study implements the Proof of Reserve (PoR) method in a blockchain-based shipment data validation system to support data integrity, authenticity, and reliability. The system was developed on a single server with three CouchDB nodes, consisting of one primary node and two backup nodes. Each shipment record was processed using the SHA-256 hashing algorithm and linked through interconnected prev_hash values to form a cryptographic data chain. This structure enables data modifications to be detected through hash inconsistency across the stored records. Validation was performed using a majority consensus mechanism among the nodes, classifying data as VALID or INVALID based on hash consistency. Simulations conducted in Jupyter Notebook showed that the system could detect data manipulation in both single-node and multi-node scenarios. The system also included an auto-recovery mechanism to restore corrupted or manipulated nodes using data from valid nodes. In addition, the prototype was developed into a web-based interface for real-time shipment tracking number verification. The results indicate that the PoR method can help maintain the consistency, transparency, and accountability of shipment data without requiring a full blockchain implementation.